Saturday

April 18, 2015

April 18, 2015

Posted by **lala** on Tuesday, February 22, 2011 at 7:56am.

- Math -
**Brian**, Tuesday, February 22, 2011 at 8:04am=x^2+4x+4+x^2+6x+8

=2x^2+10x+12

=2(x^2+5+6)

=(x+2)(x+3)

=x=-3,-2

- Math -
**Reiny**, Tuesday, February 22, 2011 at 8:56ampicking up from Brian's third-last line

= 2(x^2+5+6)

should have been

= 2(x^2+5x+6)

= 2(x+2)(x+3)

This is the fully factored form, there was no equation to "solve"

**Answer this Question**

**Related Questions**

mathematics - Key: logx= log base x 1. Prove that: (logx64 +logx4 -logx8)/(...

math - factorize :x2-2X+xy-2y

math - factorize 1) x^2=5x-6 2) 6x^2-20=-7x 3) 6x^2-7x=-2

Math IB SL - Factorize: 2x^2-xy-6y^2 ????

math - Factorize the following: 2x^2 + 3x - 7

math - Please Factorize it- 4*x^3-4*x

math - Please Factorize it- 16*x^2+8*x-1

MATH - Factorize the following : x4-x2-6 HELP!!!!!!

MATH - Factorize the following : x4-x2-6 HELP!!!!!!

math - Factorize b^4-16 PS. "b" is really the letter b